Taguchi optimization of process parameters on the hardness and impact energy of aluminium alloy sand castings (2013)
An optimization technique for sand casting process parameters based on the Taguchi method is reported in this paper. While keeping other casting parameters constant, aluminium alloy castings were prepared by sand casting technique using three different parameters, namely the mould temperature, pouring temperature and runner size. Hardness and impact energy tests were done for the resulted castings. The settings of parameters were determined by using the Taguchi experimental design method. The level of importance of the parameters on the hardness impact energy was determined using the analysis of variance (ANOVA). The optimum parameter combination was obtained by using the analysis of signal-to-noise (S/N) ratio. Analysis of the results shows that 100°C mould temperature and 700°C pouring temperatures are optimal values for hardness and impact energy. However 200 mm2 and 285 mm2 runner sizes are the optimal values for hardness and impact energy respectively. The mould temperature was the most influential parameter on the hardness impact energy of the castings.